PROMOTION OF STUDENT SELF-DIRECTION IN COOPERATIVE LEARNING IN UNIVERSITY - Strods, Gunārs (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
This article presents results of implementation of principles of direction and liberalization in cooperative learning in teacher training. The purpose of the study was to work out and implement an educational model for promotion of student self-directed learning skills in teacher training in university, and explore the relationships between the cooperative learning process and self-directed learning development. Empirical data were collected through self-directed learning-readiness tests (SDLRS/LPA), student self-assessment questionnaires, and interviews at the beginning and the end of the semester. The data of experiment group were compared with control group data, and 170 students were involved in the study. Results indicate that self directed learning readiness improves through cooperative learning processes for students of all levels, while in traditional process below average and average level students’ readiness improves, and above average level students’ readiness expressions are limited and readiness for self-direction decreases.